2015
DOI: 10.12816/0017724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advertisement on Consumer Choice : A Case of SME and Consumers

Abstract: With some examples of advertisements we have print ads, radio and television commercials, infomercials, advertorials, and billboards and kiosks-both of which may be stagnant or interactive. All these communication means are very expensive for corporates. When a company faces a crisis, advertising is usually the first item that is cut from budgets in order to face that economic crisis. However we have to recognize the fact that advertising is the most accurate instrument in terms of carrying, evaluating a produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nour et al (2014) found out that in Jordan, advertisements highly affect consumers purchase decision. Habib et al (2015) stated that there is a positive significant relationship between advertisement exposure and consumers purchase decision. Fatima and Lodhi 2015found that there is a positive significant impact of advertisements on consumer purchase decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nour et al (2014) found out that in Jordan, advertisements highly affect consumers purchase decision. Habib et al (2015) stated that there is a positive significant relationship between advertisement exposure and consumers purchase decision. Fatima and Lodhi 2015found that there is a positive significant impact of advertisements on consumer purchase decision.…”
Section: Discussionmentioning
confidence: 99%
“…Construct validity was established based on Pearson correlation coefficient; the results are presented in Table 2. (Costa, 2014) (Deepa, 2013) (Sachdeva, 2016) 4 Statements Evaluation of Alternatives (Costa, 2014) 3 Statements Purchase Decision (Costa, 2014) (Habib et al, 2015) (Gao et al, 2005) 4 Statements…”
Section: Construct Validitymentioning
confidence: 99%
“…In order to evaluate consumer purchasing choice in retailer stores in Erbil, this research examined and assessed the relationship between types of advertisement consumer purchasing choice. The questionnaire was adapted from previous studies (Hampel, et al, 2012, Hameed , et al, 2014, Habib,et al, 2015, the respondents were asked to rate how much they agree on each item according to the five point likret scales, ranging from 1= Strongly Disagree to 5= Strongly Agree. Table 1 demonstrates the demographic analysis for the participants; it was found that 159 male participants participated in this study and 109 participants participated, moreover it was found different aged of participants participated as follow; 29 participants fall into group of 20-25 years old, 43 participants fall into group of 26-30 years old, 78 participants fall into group of 31-35 years old, 68 participants fall into group of 36-40 years old, 21 participants fall into group of 41-45 years old, 18 participants fall into group of 46-50-years old and 11 participants fall into group of 50 years and above.…”
Section: Methodsmentioning
confidence: 99%
“…are in the focus of many Russian and foreign researchers. Numerous studies investigate the advertising effectiveness (Kehinde et al 2016 ; Weber and Schweiger 2017 ), technologies (Polukarov et al 2016 ; Borisov 2017 ), its influence on consumer behaviour (Habib et al 2015 ; Oboznaya 2017 ; Haider and Shakib 2018 ) and on the formation of consumers’ attitudes (Rai 2013 ; Arnaud et al 2018 ; Subroto and Samidi 2018 ), its psychological effects (Pechmann and Catlin 2016 ; Torres 2020 ), and novel marketing channels (Knoll 2016 ; Pütter 2017 ; Yang et al 2017 ). Particular attention is paid to new types of advertising: the so-called green advertising based on an ecological approach (Mkik et al 2017 ) and native advertising, which is believed consumer-friendly due to the lack of obvious pressure on the client (Laursen 2017 ).…”
Section: Introductionmentioning
confidence: 99%